A New Path for Women's Justice at Workplace - ICC and LCC in Organized and Unorganized Sector under POSH Act 2013 - Dr. Monika Sharma,, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper explores the establishment and effectiveness of the Internal Complaints Committee (ICC) and the Local Complaints Committee (LCC) under the Prevention of Sexual Harassment (POSH) Act of 2013. The focus is on their roles in both organized and unorganized sectors, assessing their impact on fostering a safer workplace for women. The study analyzes challenges, successes, and areas for improvement in implementing these mechanisms to ensure justice for women in the workplace.